Contemporary women's secure psychiatric services in the United Kingdom: A qualitative analysis of staff views. Issue 9 (5th September 2017) - Walker, T.; Edge, D.; Shaw, J.; Wilson, H.; McNair, L.; Mitchell, H.; Gutridge, K.; Senior, J.; Sutton, M.; Meacock, R.; Abel, K.
Accessible summary: What is known on the subject?: Three pilot UK‐only Women's Enhanced Medium Secure Services (WEMSS) was opened in 2007 to support women's movement from high secure care and provide a bespoke, women‐only service. Evidence suggests that women's secure services are particularly challenging environments to work in and staffing issues (e.g., high turnover) can cause difficulties in establishing a therapeutic environment. Research in this area has focused on the experiences of service users. Studies which have examined staff views have focused on their feelings towards women in their care and the emotional burden of working in women's secure services. No papers have made a direct comparison between staff working in different services. What does this study add to existing knowledge?: This is the first study to explore the views and experiences of staff in the three UK WEMSS pilot services and contrast them with staff from women's medium secure services. Drawing upon data from eighteen semi‐structured interviews (nine WEMSS, nine non‐WEMSS), key themes cover staff perceptions of factors important for women's recovery and their views on operational aspects of services. This study extends our understanding of the experiences of staff working with women in secure care and bears relevance for staff working internationally, as well as in UK services. What are the implications for practice?: The study reveals the importance of induction and training for bank and agency staff working in women's secure services. Further, regular clinical supervision should be mandatory for all staff so they are adequately supported. Abstract: Introduction: Women's Enhanced Medium Secure Services (WEMSS) is bespoke, gender‐sensitive services which opened in the UK in 2007 at three pilot sites. This study is the first of its kind to explore the experiences of WEMSS staff, directly comparing them to staff in a standard medium secure service for women. The literature to date has focused on the experiences of service users or staff views on working with women in secure care. Aim: This qualitative study, embedded in a multimethod evaluation of WEMSS, aimed to explore the views and experiences of staff in WEMSS and comparator medium secure services. Methods: Qualitative interviews took place with nine WEMSS staff and nine comparator medium secure staff. Interviews focused on factors important for recovery, barriers to facilitating recovery and operational aspects of the service. Discussion: This study provides a rare insight into the perspectives of staff working in UK women's secure services, an under‐researched area in the UK and internationally. Findings suggest that the success of services, including WEMSS, is compromised by operational factors such as the use of bank staff. Implications for practice: Comprehensive training and supervision should be mandatory for all staff, so best practice is met and staff adequately supported.